Distribution of High-risk Human Papillomavirus Genotypes in Cervical Smear Samples and Evaluation of ASC-US, LSIL, and HSIL Results - Eylul Beren Tanik; Ayfer Bakir; Tugba Taskin Turkmenoglu; Gul Erdem (Journal of Cytology)
Context:High-risk human papillomavirus (hrHPV) is the most common viral pathogen responsible for cervical cancers. Determining the rates of HPV positivity, genotypic distribution, and obtaining regional epidemiological data can provide guidance for preventive strategies.